Pengaruh Bauran Pemasaran (Marketing Mix) Terhadap Keputusan Pembelian Pisang Sunpride (Studi Kasus: Supermarket Superindo Tropodo) - Adinda Nurul Izmi; Sri Tjondro Winarno; Prasmita Dian Wijayati (Universitas Batanghari Jambi, 2023)
This research was conducted with the aim of describing the characteristics of cavendish sunpride banana consumers at Superindo Tropodo, to analyze the marketing mix which consists of product, price, place, promotion, people, process, physical evidence influences consumer decisions in purchasing cavendish sunpride bananas at Superindo Tropodo, to analyze which marketing mix variables have the most influence on consumer decisions in purchasing cavendish sunpride bananas at Superindo Tropodo. The analysis technique and hypothesis testing in this study used Partial Least Square (PLS) with the help of Warp PLS software. The use of the PLS method as an analytical technique and hypothesis testing has advantages such as the sample size does not have to be large and can be used to develop a theory. The results of this study are the characteristics of respondents based on the gender of the majority of respondents with female. Characteristics of respondents based on the age of the majority of respondents aged 20-30 years. The characteristics of respondents based on their last education were the majority of Bachelor / Equivalent education level. Characteristics of respondents based on the work of the majority of respondents whose jobs are the most are self-employed. Characteristics of respondents based on the income of the majority of respondents whose income is the largest, namely income above Rp. 4,000,000. Product variables, price, place, promotion, people, process, physical evidence have a positive and significant effect on purchasing decisions. The physical evidence variable that has the most high influence on purchasing decisions.